Effect of Coating Materials and Storage Temperatures on Quality and Shelf Life of Papaya Fruit - Bambang S. Purwoko; P. Fitradesi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2000)
The objective of the research was to determine the effect of coating materials and storage temperatures in inhibiting the ripening process of papaya fruits. A two-factor factorial experiment was conducted. Replicates were three times and functioned as block. It consisted of coating material factor i.e. control, Semperfresh0 ,8% carnauba wax 6% and bee wax 6% and storage temperature factor, control room (27-31°C) and cool (18-20